Analysis of gene expression profiles of multiple skin diseases identifies a conserved signature of disrupted homeostasis. Issue 9 (30th July 2018) - Mills, Kevin J.; Robinson, Michael K.; Sherrill, Joseph D.; Schnell, Daniel J.; Xu, Jun
Abstract: Triggers of skin disease pathogenesis vary, but events associated with the elicitation of a lesion share many features in common. Our objective was to examine gene expression patterns in skin disease to develop a molecular signature of disruption of cutaneous homeostasis. Gene expression data from common inflammatory skin diseases (eg psoriasis, atopic dermatitis, seborrhoeic dermatitis and acne) and a novel statistical algorithm were used to define a unifying molecular signature referred to as the "unhealthy skin signature" (USS). Using a pattern‐matching algorithm, analysis of public data repositories revealed that the USS is found in diverse epithelial diseases. Studies of milder disruptions of epidermal homeostasis have also shown that these conditions converge, to varying degrees, on the USS and that the degree of convergence is related directly to the severity of homeostatic disruption. The USS contains genes that had no prior published association with skin, but that play important roles in many different disease processes, supporting the importance of the USS to homeostasis. Finally, we show through pattern matching that the USS can be used to discover new potential dermatologic therapeutics. The USS provides a new means to further interrogate epithelial homeostasis and potentially develop novel therapeutics with efficacy across a spectrum of skin conditions. Abstract :